Hubungan Stres Dengan Tekanan Darah Pada Lansia - Kristina Pae; Maria Manungkalit; Paulina Nona Reni (JURNAL NERS LENTERA, 2023)
Age-related increases in blood pressure are normal, but persistently high blood pressure can harm the heart, blood vessels, and other organs. Stress triggers hypertension by activating the sympathetic nervous system, causing blood pressure to increase erratically. Correlational analytic with cross sectional approach was used as the design of this research. The independent variable of this study is stress while the dependent variable is blood pressure. The population in this study were all the elderly at Griya Wherda Jambangan Surabaya. The sampling technique used was purposive sampling so that 30 elderly people were selected as respondents. The stress measuring tool used the Perceived Stress Scale (PSS-10) and the respondent's blood pressure measurement used sphygmomanometer. The results of the Pearson correlation test between stress and systolic blood pressure in the elderly obtained a value of r = 0.036, p = 0.851 while stress and diastolic blood pressure in the elderly obtained a value of r = 0.131, p = 0.489. These results prove that there is no relationship between stress and blood pressure in the elderly. Increased blood pressure is not only caused by stress but there are other factors that also affect both internal and external factors of the elderly.